Can selective retroperitoneal lymphadenectomy be better than unilateral retroperitoneal lymphadenectomy? - Homero O. Arruda (International Brazilian Journal of Urology, 2003)
OBJECTIVE: To propose a new modality of retroperitoneal lymphadenectomy as a complementary treatment for patients with high risk, stage I nonseminomatous testicular tumor. MATERIALS AND METHODS: We studied 76 patients with stage I nonseminomatous testis tumor (T1-T4, NX, M0) treated by orchiectomy and retroperitoneal lymphadenectomy. Among them, 33 patients underwent unilateral retroperitoneal lymphadenectomy (URL) and 43 selective retroperitoneal lymphadenectomy (SRL). URL consisted in removing the lymph nodes located around the great vessel homolateral to the tumor (aorta or vena cava and iliac vessels), and anterior and posterior to the contralateral great vessel (aorta or vena cava). SRL was performed removing the lymph nodes located anterior and between the great vessels (aorta or vena cava) and laterally to the homolateral great vessel, extending the distal dissection until the level of inferior mesenteric artery. In these groups of patients, the incidence of disease recurrence, disease-free survival index, and frequency of post-operative aspermia were assessed. Mean post-operative follow-up time was 96 months. RESULTS: In the SRL group there was only 5% of aspermia versus 79% in the URL group (p < 0.0001). Tumor recurrence was observed in only 5 of the 76 patients and was not related to the surgical technique. The disease-free survival rate after the mean follow-up of 96 months was similar in both groups, being 94% in the SRL group and 93% in the URL group. CONCLUSION: The selective retroperitoneal lymphadenectomy constitutes an effective technique with a lower morbidity than unilateral lymphadenectomy, representing an excellent option for the management of patients with high-risk, stage I nonseminomatous testis tumor.